Piety in Thoughts of John Wesley And Friedrich Schleiermacher - Bobby Kurnia Putrawan; Ludwig Beethoven Jones Noya (Jurnal Jaffray, 2020)
It is a misconception to identify modernity with secularization. When modernity simply creates the potential platform for secularization. On the one hand, modernity lessens the influence of piety to a minimum, and on the other hand, it restores piety and even modernizes piety without secularization. This essay focuses on telling the story of modernity in attempting to build a knowledge of God through the lens of piety. It centers on the work of two modern theologians: John Wesley and Friedrich Schleiermacher. The juxtaposition of Wesley and Schleiermacher is not without reason. Both of them are strongly influenced by the Moravian Brethren, which heavily emphasized a pietistic element in their community. This essay, however, will not explain the teaching of Moravian Brethren other than presenting their pietistic emphasis that was retained in Wesley and Schleiermacher's works. This essay argues that Schleiermacher's notion of a feeling of absolute dependence’ fills the rational gap of Wesleyan pietistic concept. It also discusses how the ‘Evangelical Revival/First Great Awakening’ and ‘Romanticism’ shaped Wesley and Schleiermacher, respectively, as they formulated their concept of piety. This essay is structured as follows. First, it presents the Evangelical Revival/First Great Awakening as the historical backdrop of Wesley's thought and continues with exhibiting Wesley’s concept of piety. Then, the essay describes the Romantic era and Schleiermacher's idea of piety.Adalah sebuah miskonsepsi untuk mengidentifikasi modernitas dengan sekularisasi, ketika modernitas hanya sekedar menciptakan panggung yang potensial untuk sekularisasi. Di satu sisi, modernitas mengurangi pengaruh kesalehan hingga taraf minimal, namun di sisi lain, modernitas memulihkan kesalehan. Makalah ini berfokus dalam menceritakan ulang kisah modernitas dalam upaya membangun pengetahuan akan Allah melalui lensa kesalehan. Makalah ini memusatkan diri pada karya dua teologi modern: John Wesley dan Friedrich Schleiermacher. Penjajaran Wesley dan Schleiermacher bukan tanpa alasan. Keduanya sangat dipengaruhi oleh Persaudaran Moravianyang sangat menekankan pada elemen kesalehan dalam komunitas mereka. Makalah ini, bagaimanapun, tidak menjelaskan pengajaran Persaudaraan Moravian selain menyajikan penekanan kesalehan yang dipertahankan dalam karya Wesley dan Schleiermacher. Makalah ini berupaya untuk menunjukkan bahwa gagasan Schleiermacher tentang perasaan akan ketergantungan absolut mengisi celah rasional dari konsep kesalehan John Wesley. Makalah ini juga membahas bagaimana Evangelical Revival/First Great Awakening dan Romantisisme membentuk Wesley dan Schleiermacher kala mereka merumuskan konsep kesalehan mereka masing-masing. Untuk mendukung argumen ini, makalah ini disusun sebagai berikut. Pertama, makalah ini menyajikan Evangelical Revival/First Great Awakening sebagai latar sejarah dari pemikiran Wesley dan dilanjutkan dengan menyajikan konsep kesalehan Wesley. Kemudian, makalah ini menjelaskan era Romantis dan konsep kesalehan Schleiermacher.